Exploring the Role of Transformational Leadership in Boosting Lecturer Commitment and Performance in Islamic Higher Institutions - Munajim, Ahmad; Acharjya, Vasavvi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
Transformational leadership, affective commitment, and performance play critical roles in enhancing academic excellence in higher education. This study investigates the direct and indirect effects of transformational leadership on lecturer performance in Islamic higher education institutions, with affective commitment as a mediating variable. Specifically, it explores the impact of four leadership dimensions: ideal/charismatic influence, inspirational motivation, individual consideration, and intellectual stimulation. Using a quantitative survey method, data were collected from 148 certified lecturers through a structured questionnaire. Structural Equation Modelling (SEM) and path analysis were employed, yielding an acceptable model fit (CFI > 0.9, RMSEA < 0.08). Results indicate a significant positive relationship between transformational leadership and lecturer performance, both directly and through the mediating effect of affective commitment. Among the leadership dimensions, inspirational motivation and individual consideration had the most decisive influence on affective commitment. This research provides empirical evidence of the effectiveness of transformational leadership in improving lecturer performance and offers insights for leadership development in academic institutions. Future studies are encouraged to expand the scope, employ mixed methods, and investigate additional variables to further deepen the understanding of these relationships.